Phylogenetic and antigenic analyses of coxsackievirus A6 isolates in Yamagata, Japan between 2001 and 2017. Issue 8 (14th February 2019) - Mizuta, Katsumi; Tanaka, Shizuka; Komabayashi, Kenichi; Aoki, Yoko; Itagaki, Tsutomu; Katsushima, Fumio; Katsushima, Yuriko; Yoshida, Hiroshi; Ito, Sueshi; Matsuzaki, Yoko; Ikeda, Tatsuya
Highlights: Strains in 2001–08 and in 2010–17 were clearly clustered separately. There were cross-antigenicities among different cluster/subgenotype strains. Vaccination will be effective, irrespective of genetic cluster/subgenotype. Abstract: Although coxsackievirus A6 (CV-A6) is generally recognized as a causative agent of herpangina in children, CV-A6 infections globally emerged as a new and major cause of epidemic hand-foot-and-mouth-diseases (HFMDs) around 2008. To clarify the longitudinal epidemiology of CV-A6, we carried out sequence and phylogenetic analyses for the VP1 and partially for the VP4-3D regions as well as antigenic analysis using 115 CV-A6 isolates and 105 human sera in Yamagata, Japan between 2001 and 2017. Phylogenetic analysis revealed that CV-A6 isolates were clearly divided into two clusters; strains in circulation between 2001 and 2008 and those between 2010 and 2017. Neutralizing antibody titers of two rabbit antisera, which were immunized with Yamagata isolates in 2001 and 2015, respectively, against 28 Yamagata representative strains as well as the prototype Gdula strain were 1:2560–1:5120 and 1:160–1:640, respectively. The neutralizing antibody titers among residents in Yamagata against the above two strains were similar. Our analyses revealed that there were cross-antigenicities among all analyzed CV-A6 strains, although the newly emerged strains were introduced into Yamagata around 2010 and replaced the previous ones. With regard to control measures, these findings suggest that we can prevent CV-A6 infections through the development of a vaccine that effectively induces neutralizing antibodies against CV-A6, irrespective of genetic cluster.